Diversidade e distribuição espacial de Elmidae (Coleoptera) no estado do Rio Grande do Sul - Braun, Bruna Marmitt (2018)
The objective of this study was to i) Analyze how the assemblages of larvae and adults of Elmidae respond to forest conversion in a subtropical area preserved in semideciduous Atlantic Forest; ii) Evaluate the influence of different buffers of riparian vegetation (more than 40 m wide to less than 5 m) and substrate types (sedimentary and organic), as well as their interaction in the community structure of Elmidae; iii) Model the potential distribution of Elmidae taxa in the extreme south of Brazil, in relation to climatic and landscape environmental predictors (topography, hydrology and land cover) using species distribution models (SDM). In addition, we estimated the similarity in the predicted distribution of the modeled taxa in order to investigate the niche similarity between the genera Elmidae and Macrelmis. Forest integrity was an important factor for the structuring of Elmidae communities, where in the converted areas the lowest abundances of elmidae individuals were found. The larvae and adult stages were affected by deforestation, just as the structure of the communities was distinct between deforested and forested areas. Width of riparian vegetation and type of substrate were also factors that influenced the structuring of communities. The results showed that the communities were influenced by marked differences in widths of riparian vegetation. Only the relative abundance of the genera of Elmidae and their stages of life were different between the wide widths of vegetation. On the other hand, the strong influence of the substrate type (organic and inorganic) on the structure of the neotropical macroinvertebrate community was corroborated. The potential distribution of species showed a relation of landscape and environmental factors of large scale with structures of genera and species of Macrelmis. Factors such as declivity, precipitation, and ecoregions were important for structuring the communities of genera and species, but we verified that there may be an interaction between the predictors on a regional and local scale. It is critical to understand the complex relationships between large-scale diversity patterns and the local ecological characteristics of species. The modeling techniques are an effective tool to indicate areas for future sampling efforts and thus to know the diversity of the Elmidae family in southern Brazil.